Pengaruh Penggunaan Puzzle Games Terhadap Perkembangan Sosial Emosional Anak Usia Dini di Pos Paud Harapan Putera Galuh - Masitoh, Iis Imas; Nugraha, Anggi Purwa; Ihsanda, Nu'man (JOECE: Journal of Early Childhood Education, 2024)
This study aims to determine the effect of using Puzzle Games on the social-emotional development of children aged 4-5 years at Pos PAUD Harapan Putera Galuh, Cidolog District, during the 2023/2024 academic year. This research employed a quantitative method with a Pre-Experimental One Group Pretest-Posttest design. The sample consisted of 16 children, and data were collected through observations using an assessment rubric. The pretest results showed that 81% of the children were in the Not Yet Developed (NYD) category, while 19% were in the Beginning to Develop (BTD) category. After the intervention, the posttest results revealed that 81% of the children were in the Beginning to Develop (BTD) category, and 19% were in the Developing as Expected (DAE) category. Hypothesis testing indicated an Asymp.Sig. (2-tailed) value of 0.000 (<0.05), confirming the hypothesis. Thus, it can be concluded that using Puzzle Games significantly affects young children's social-emotional development.